PROGRAM COOPERATIVE LEARNING PEMBUATAN KAIN TIE-DYE SHIBORI PADA KELOMPOK PKK KELURAHAN RANGKAPAN JAYA BARU - Nasution, Siti Rohana; Zulaihah, Lilik; Rahayu, Fajar; Mahfud, Halim; M, Nantia Rena Dewi (Jurnal Serina Abdimas, 2023)
ABSTRACT Cooperative Learning The motive of the shibori tie-dye technique in the PKK Group of Parung Confused Village, Rangkapan Jaya Baru Village, Pancoran Mas District, Depok with this learning model which aims to be able to grow the hardness of the community so that it is able to carry out small business activities for the community, especially PKK mothers and youth groups of coral cadets so that it becomes a group of people who have not been productive into productive communities. The Partnership Program was carried out with 20 PKK members and 10 young women members of Karang Taruna Kampung Parung Confused. The training given starts from folding techniques to get designs and motifs, harmonious coloring techniques so that there are various variations. Natural coloring techniques by exploring plants to get color. The form of learning with the concept of students learning and working by forming small groups or groups consisting of 4 to 6 participants collaboratively and heterogeneously. With the coorperative learning system, it is expected to foster moivation and organize dynamic group work so that the partnership program can meet its goals. ABSTRAK Cooperative Learning Motif teknik tie-dye shibori pada Kelompok PKK Kampung Parung Bingung Kelurahan Rangkapan Jaya Baru Kecamatan Pancoran Mas Depok dengan model pembelajaran ini yang bertujuan untuk dapat menumbuhkan daya kerasi masyrakat sehingga mampu untuk melakukan kegiatan usaha kecil bagi masyrakat terutama ibu-ibu PKK dan kelompok remaja karang taruna sehingga menjadi kelompok masyarkat yang belum produktif menjadi masyarkat yang produktif. Program Kemitraan dilaksanakan dengan jumlah peserta sebanyak 20 anggota PKK dan 10 orang remaja putri anggota Karang Taruna Kampung Parung Bingung. Pelathan yang diberikan mulai dari Teknik pelipatan untuk mendaptakan desain dan motif, Teknik pewarnaan yang harmonis sehingga didaptakan variasi beragam. Teknik pewarnaan alami dengan mengekplorasi tumbuh-tumbuhan untuk mendpatkan warna. Bentuk pembelajaran dengan konsep peserta didik belajar dan bekerja dengan membentuk kelompok kecil atau group terdiri dari 4 sampai 6 peserta secara kolaboratif dan bersifat heterogen. Dengan system pembelajaran coorperative learning diharapkan dapat menumbuhkan moivasi dan berorganisasi kerja kelompok yang dinamis sehingga program kemitraan dapat memenuhi tujuannya.